Efektifitas Intervensi Psikologi Positif Terhadap Kesejahteraan Psikologis : Tinjauan Literatur Sistematis : Tinjauan Literatur Sistematis - Khatimah, Husnul; Tondok, Marselius Sampe (Syntax Corporation, 2025)
Increasing stress, anxiety and pressure conditions in various ways make most people experience a decrease in psychological well-being, especially among Generation Z today. One of the interesting approaches to be studied further to improve psychological well-being is positive Psychological Interventions. This study aims to evaluate the effectiveness of positive psychological interventions on psychological well-being. This study is a Systematic Literature Review (SLR) using the PRISMA guidelines, with literature searches on Google Scholar, PubMed, ScienceDirect, and SagePub databases in the range of 2013–2023. The results of the selection screened 6 studies that met the inclusion criteria, namely experimental research based on Randomized Controlled Trial (RCT). The results of the analysis showed that positive psychology interventions, such as mindfulness, gratitude, optimism, and approaches based on the PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) model, were proven to improve psychological well-being. The reviewed studies revealed that positive psychological interventions are able to increase happiness, reduce stress and depression, and increase individual resilience in the face of life's challenges.